Validation of the Chinese version of the Yale-Brown Obsessive Compulsive Scale for Pathological Gambling for individuals with gambling disorder in Mainland China - Fan, Dongli; Zhang, Xiyuan; Shi, Siyao; Liu, Jingyang; Wei, Yicheng; Song, Ge; Zhou, Yiyi; Zhu, Yuanyuan; Shi, Jingyun; Cai, Xingshi; Zhong, Gangliang; Du, Jiang (Frontiers in Psychiatry, 2025)
IntroductionThe escalating severity of gambling issues in China highlights the need for culturally adapted assessment tools. The Yale-Brown Obsessive Compulsive Scale for Pathological Gambling (PG-YBOCS) is recognized for its ability to assess both the severity and compulsive features of gambling disorder.MethodsGiven its emphasis on the compulsive features of gambling disorder, this study aimed to validate the Chinese version (PG-YBOCS-C) in clinical assessment. The 10-item PG-YBOCS-C was developed through translation and expert review. A total of 116 individuals with gambling disorder were recruited.ResultsReliability was assessed using Cronbach’s α coefficient (0.958) and test-retest reliability (0.722). The content validity index was 0.912, with item-level indices ranging from 0.778 to 1.000. Bartlett’s test of sphericity yielded X2 = 1123.86, P<0.001, and the KMO measure was 0.93. Exploratory factor analysis identified a single principal component accounting for 72.8% of the variance.DiscussionThe reliability and validity of PG-YBOCS-C have been demonstrated, establishing it as a dependable tool for evaluating the severity of gambling symptoms in Chinese individuals.